(3GdcdGH ai eUQ GdbOjeI (B/ s - (3eGjSg QHjY bGSe YeQGfs; (3gHI eUWai ceGd fhM (B: s ((3GdbGgQI (B: s (3eGjSg QHjY bGSe YeQGf (B: s, 2016)
(3GdcdH gh CbOe GdMjhGfGJ GdoeSJCfSg ai GdYGde(B: (3hgfGc NdGa Mhd Sda GdcdH(B: (3dcf GdCcKQ EMJeGdkG gh GdPFH HSHH GdeejRGJ GdJTQjMjg hGdSdhc GdELJeGYi GdeJTGHg(B: (3hai YGe (B2013: (3CKHJJ JMdjdGJ GdMeV Gdfhhi Cf cd GdcdGH GdJi JMjG Gdjhe JQLY Edi CQHY SdGdGJ Ljfjg(B: (3fTCJ cdgG ai ChQhHG(B: (3hCf GdJQGHW Gdbhi Hjf GdEfSGf hGdcdH(B: (3XgQ eG Hjf (B19.000 (3h(B30.000 (3YGe eVi ef GdeMJed ai SjGb GdUjO(B. (3* GdcdH gh CbOe Qajb ddEfSGf ai eUQ(B: (3MjK oYKQ Ydi HbGjG YXe cdH ai eQeOI Hfi SdGeg MhGdi (B5400- 4500 (3b(B. (3e(B.: (3hoUhQ GdcdH ceYGhf ddQLd ai GdUjO efP YUhQ eG bHd GdJGQjN(B. (3* ESJNOeJ GddZg GdeUQjg GdbOjeg KdGK cdeGJ ddJYHjQ Yf GdcdH hgPg GdcdeGJ gi(B: Tsm: iw: iwiw: (3hcdeI (BTsm (3gi GdCbOe(B: (3CqeG cdeJi (Biw: iwiw (3aefP GdOhdg GdhSWi heUOQgeG fHGM GdcdH(B. (3* oPcQ GdcdH ai GdfUhU GdCOHjg hGdOjfjg(B: (3hdbO OGQ gPG GdPcQ eG Hjf Gdbjeg hGdOfh(B: (3aai GdfUhU GdCOHjg jXgQ GdWGHY GdEjLGHi ai ESJdgGe UaI GdhaGA hGdWGYg hGdYQaGf HGdLejd GdfGHYg ef MH GdcdH dSjOg(B: (3hjXgQ GdWGHY GdSdHi ai ESJdgGe WGHY GdJPdd ef GdcdGH GdVGdg(B: (3hPdc YfO GdJTHg Ch GdJTHjg HGdcdH(B: (3CqeG ai GdfUhU GdOjfjg(B: (3jXgQ GdWGHY GdEjLGHi ai EcJSGH GdeJhai GdWjH dSQYI GdcdH ai ELJjGR eNGWQ GdYGde GdBNQ(B: (3CqeG GdeJhai GdYGUi aojTqHg HGdcdH GdegRhe(B: (3hojCcd ef pbHd eYHhO Ph hLg cdH hLSO EfSGf hgh GdeYHhO (Bam.w HH (3Ci HGdY Gdedjhf(B. (3* CWdb GdeUQi GdbOje CSeGA TNUjg Ydi cdGHg JLGhRJ GdKeGfjf CSekG(B: (3efgG CSeGA edhc hCaQGO(B. (3* JYOOJ ChVGY JUhjQ GdcdH cQajb oeMHH hMGQS TNUi ai GdefGXQ GdeUQjI GdbOjeI(B: (3hgi Gdhbha(B: (3GdeTi(B: (3GdEJcGA Ydi GdbGFeJjf GdNdajJjf(B: (3GdLKhe Ydi GdbhGFe GdCQHYg hQaY GdQCS(B: (3GdLKhe Ydi GdbhGFe GdCQHYg hSfO GdQCS Ydi GdCQV(B: (3hJYOOJ CeGcf JUhjQ GdcdH HGdbQH ef UGMH GdebHQg(B: (3hhUdJ Edi (B13 (3ehVY(B: (3hdjS CSad Ch HLhGQ ebYO UGMHg abW(B. (3* ESJYGf GdeUQi GdbOje HGdcdGH ai GdUjO efP YUhQ eG bHd GdJGQjN(B: s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdBKGQ GdeUQjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMjhGfGJ GdCdjag s; (3GdcdH s; (3Sdhbi s